Corporate tax avoidance and stock price crash risk: the moderating effects of corporate governance - Thai, Hanh Minh; Dang, Khue Ngoc; Nor, Normaziah Mohd; Nguyen, Hien Thi (Emerald Publishing, 2025)
Purpose: This study aims to investigate the relationship between corporate tax avoidance and stock price crash risk and the moderating effects of corporate governance. Design/methodology/approach: This study investigates the relationship between corporate tax avoidance and stock price crash risk using the sample consisting of listed firms in Vietnam for the period of 2011–2020 using panel regressions. Findings: The authors find that there is a positive relationship between tax avoidance and stock price crash risk. Foreign ownership weakens the impacts of tax avoidance on stock price crash risk, while managerial ownership strengthens the impacts. Female Chief Executive Officers (CEOs) and female chairpersons weaken this relationship. Board gender diversity and state ownership have insignificant moderating impacts. Practical implications: These findings could help the stock market build better internal monitoring mechanisms to reduce the impacts of tax avoidance on future stock price crash risk. Investors can recognize the characteristics of corporate governance, especially foreign ownership, managerial ownership, female CEOs and female chairpersons when making investment decisions. The policy makers should consider policies to attract foreign investment and support women entrepreneurship. Originality/value: This paper contributes to the literature on the impacts of tax avoidance on stock price crash risk in emerging countries. This paper is the first to investigate the influence of corporate governance mechanisms including state ownership, foreign ownership, female CEOs and chairpersons and board gender diversity on this relationship.